STRATEGI PUBLIC RELATIONS PT.PLN (persero) WILAYAH RIAU dan KEPULAUAN RIAU DALAM PENGELOLAAN PESAN PENCABUTAN SUBSIDI LISTRIK TEPAT SASARAN DI KOTA PEKANBARU - Larasati, Dwi Sekar; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Issues that are spread in most societies have the potential to become a crisis if not handled properly, Especially if it has entered a crisis phase that requires full attention to its management. Electricity subsidies, which are actually subsidies provided by the government to poor people, but it turns out that when the data review was conducted, it was found that many people in the able category were able to get it, this review was carried out by the TNP2K team (national team for accelerating poverty reduction). However, since the emergence of information related to the revocation of electricity subsidies on target, the public relations of PT. PLN (Persero) in the Riau and Riau Islands regions did not immediately provide clarification and also a press conference but prefer to find out in advance related to the issue. The purpose of this study is to look at the steps taken by PR and also the form of communication strategies with the media carried out in the management of the communication crisis the removal of electricity subsidies on target. The research method used in this study is a qualitative method by determining 3 (three) research subjects as informants through a purposive technique. Public Relations Strategy PT. PLN (Persero) Riau and Riau Islands Region in managing the message of revocation of electricity subsidies right on target in the city of Pekanbaru. Data information is obtained through observation, interviews, documentation. Data analysis techniques in this study using Miles & Huberman interactive data models. Check the validity of the data using triangulation. The results showed that the Strategy of Public Relations of PT PLN (Persero) Riau and Riau Islands in managing the message of revocation of electricity subsidies on target in the city of Pekanbaru was carried out by taking a planning strategy by conducting prior review of information circulating and also monitoring the development of information, collecting data about the problems that occur and develop a resolution strategy that can be done. Maintaining good relations and also collaborating with the media that aims to provide strength for the company.Keyword : strategi, public relations, PLN, SLTS